1989
DOI: 10.1080/01411598908206833
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the shear viscosity of the system nitrobenzene—n-hexane in the critical region

Abstract: The shear viscosity of the system nitrobenzene-n-hexane was measured along the isochores near the critical concentration. By applying the empirical formula q = qids;# the critical exponent of the shear viscosity 4 was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Experiments on molecular systems indicate a very small critical exponent for the zero shear and zero frequency shear viscosity, [1][2][3][4] or a logarithmic divergence, 5 although in a few papers it is shown that the experimental accuracy is not sufficient to distinguish between the two. [6][7][8] It is also reported that neither an exponential nor logarithmic divergence occurs, but that the viscosity remains finite at the critical point.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on molecular systems indicate a very small critical exponent for the zero shear and zero frequency shear viscosity, [1][2][3][4] or a logarithmic divergence, 5 although in a few papers it is shown that the experimental accuracy is not sufficient to distinguish between the two. [6][7][8] It is also reported that neither an exponential nor logarithmic divergence occurs, but that the viscosity remains finite at the critical point.…”
Section: Introductionmentioning
confidence: 99%